2019
DOI: 10.3390/min9030182
|View full text |Cite
|
Sign up to set email alerts
|

Petrogenesis of Low Sr and High Yb A-Type Granitoids in the Xianghualing Sn Polymetallic Deposit, South China: Constrains from Geochronology and Sr–Nd–Pb–Hf Isotopes

Abstract: The nature and origin of the early Yanshanian granitoids, widespread in the South China Block, shed light on their geodynamic setting; however, understanding their magmatism processes remains a challenge. In this paper, we present both major and trace elements of bulk rock, Sr–Nd–Pb isotopic geochemistry, and zircon U–Pb–Hf isotopes of the low Sr and high Yb A2-type granites, which were investigated with the aim to further constrain their petrogenesis and tectonic implications. Zircon U–Pb dating indicates tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 70 publications
1
12
0
Order By: Relevance
“…Furthermore, the trace element tectonic environment discrimination diagram (Figure 11) indicated that all sample points for the Jinchanghe diabase were plotted on the within-plate basalt area, thus suggesting that the rocks indicated characteristics of within-plate basalt. In addition, the Jinchanghe diabase lacked HFSEs, which is consistent with the characteristics of continental rift basalt [30]. Therefore, considering the diabase distribution near the transtensional fault, these results suggest that the Jinchanghe diabase was formed in an extensional tectonic setting.…”
Section: Tectonic Environmentsupporting
confidence: 74%
“…Furthermore, the trace element tectonic environment discrimination diagram (Figure 11) indicated that all sample points for the Jinchanghe diabase were plotted on the within-plate basalt area, thus suggesting that the rocks indicated characteristics of within-plate basalt. In addition, the Jinchanghe diabase lacked HFSEs, which is consistent with the characteristics of continental rift basalt [30]. Therefore, considering the diabase distribution near the transtensional fault, these results suggest that the Jinchanghe diabase was formed in an extensional tectonic setting.…”
Section: Tectonic Environmentsupporting
confidence: 74%
“…Many tectonic models have been proposed to describe the magmatism, tectonism, and mineralization during the Yanshanian period in South China, including the rift model [18], the mantle plume model [9], and the Paleo-Pacific Plate subduction model [75]. Besides, disagreement exists among researchers about the geodynamic setting of the formation of Late Jurassic A-type granites in the southwest section of the Shihang belt [19,20,[22][23][24][25][26]29,54,[66][67][68][69][70][71][72][73][74][75][76][77][78][79][80]. According to the discriminant diagram of A-type granites proposed by Eby (1992) [64], the Xishan granites fall into the A1-type granite domain (Figure 11), which seems to fit the rift model or mantle plume model.…”
Section: Geotectonic Settingmentioning
confidence: 99%
“…This NE-trending A-type granite belt extends from the Qianlishan and Qitianling plutons in the north, through the Jiuyishan pluton in the middle section, to the Huashan-Guposhan pluton in the south (Figure 1c). The young T DM granite belt continues to extend towards the southwest until it reaches the southeast of Guangxi Province [28][29][30]. However, controversies still exist about the genesis of the Jurassic NE-trending A-type granites and their geodynamic settings [31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…The Tongtianmiao pluton has no access roads and not been studied in any detail, but both the Laiziling and Jianfengling plutons have been thoroughly researched. The Laiziling granite yields zircon U-Pb ages of 155-150 Ma (Shu et al 2011;Zhu et al 2011;Lai, 2014;Yang et al 2018;Xiao et al 2019), while the Jianfengling granite gives zircon U-Pb ages of 165-160 Ma (Xuan et al 2014;Yang et al 2018). Previous research also found that zircons from the Laiziling pluton have multiple age groups including Proterozoic (> 900 Ma), Silurian (c. 430 Ma), Triassic (c. 220 Ma), Jurassic (c. 150 Ma) and Cretaceous (c. 80 Ma).…”
mentioning
confidence: 99%